2017
DOI: 10.11159/rtese17.141
|View full text |Cite
|
Sign up to set email alerts
|

Removal of the Mixture of Azo Dyes Allura Red - Tartrazine by Adsorption onto Corncob

Abstract: -Synthetic dyes are widely used around the world, and big volumes of coloured effluents end up being discharged into water bodies. Allura Red and Tartrazine are azo dyes with a broad use spectrum mainly in food and textile industries and their removal from the aquatic ecosystems, is a challenge. In the last decades, several methods have emerged to find a solution of this environmental problem, among them, adsorption using agro-industrial by-products stands out as a high efficient and low cost metodology for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The only reported wastes (to the best of our knowledge) as adsorbents either directly or after pyrolysis for removing AR are pinewood, arabica coffee residues, coconut shell, corncob, guargum, peanut hull waste, sawdust, pecan nut shells, luffa cylindrica and bael patra. [42][43][44][45][46][47][48][49][50][51] Limited number of studies reported in this area was the impetus behind this study, which motivated us to attempt the potential of other varieties of agricultural wastes lying around us for treating wastewater in order to make it free from toxic dyes, like AR. This study aimed at investigating the efficiency of watermelon peels (WMP) waste before and after pyrolysis for AR removal from wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…The only reported wastes (to the best of our knowledge) as adsorbents either directly or after pyrolysis for removing AR are pinewood, arabica coffee residues, coconut shell, corncob, guargum, peanut hull waste, sawdust, pecan nut shells, luffa cylindrica and bael patra. [42][43][44][45][46][47][48][49][50][51] Limited number of studies reported in this area was the impetus behind this study, which motivated us to attempt the potential of other varieties of agricultural wastes lying around us for treating wastewater in order to make it free from toxic dyes, like AR. This study aimed at investigating the efficiency of watermelon peels (WMP) waste before and after pyrolysis for AR removal from wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption spectra of both dyes are partially overlapped, as it can be seen in figure 2. The quantification of BB and AR in mixture has been already studied (Villada & Hormaza, 2015;Jiménez et al, 2017) and it is performed through a mathematical model.…”
Section: Adsorption and Desorptionmentioning
confidence: 99%